(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Polyhydroxybutyrates (PHB) are bio-plastics accumulated by some bacteria living in environments where the carbon source is in excess and other nutrients are limited. The aim of this study was to screen Bacillus subtilis for accumulation of PHB, using potato peel as a carbon source. A total of 100 g of potato peels were processed and analyzed for proximate composition. A total of 25 g from 12 soil samples, including four samples from three different locations, were assayed using microbiological techniques to isolate and characterize B. subtilis. PHB accumulation was determined using Sudan Black B dye, and quantified with a spectrophotometer to identify the best-producing isolates. The production conditions, consisting of pH, NaCl concentrations, and nitrogenous sources were optimized and employed in the PHB production, with the processed peel as the sole carbon source cultured with the best isolates. The PHB was analyzed using Fourier Transform Infrared Spectroscopy (FTIR). The proximate compositions of the carbohydrate and protein in the potato peel were 55.11% and 20.38%, respectively. The occurrence rate of B. subtilis was 58.3% (7/12), with 57.14% (4/7) of these isolates being PHB producers, and 4 of them were the best producers. The optimized conditions were pH 7, 3% NaCl and NH4Cl as the nitrogen source. The PHB yield from the three best producers under the optimized conditions was three times higher. FTIR analysis confirmed the polymer as PHB. Garden soil was the best source for isolating PHB-producing B. subtilis, and potato peels were converted from waste to wealth (PHB) with a moderate yield.